Bidirectional relationship between C-reactive protein and depressive symptoms considering cumulative effect among Chinese middle-aged and older adults - Zhao, Ningxuan; Jiang, Lin; Hu, Meijing; Zhang, Baiyang; Lin, Yidie; Yao, Qiang; Hao, Jingjing; Zhu, Cairong (Frontiers in Psychiatry, 2024)
Research examining the bidirectional relationship between C-reactive protein (CRP) and depressive symptoms, while accounting for cumulative effect of repeated episodes of CRP or depressive symptoms, is currently deficient in non-Western populations.A nationally representative population-based cohort data from the Chinese Health and Retirement Longitudinal Study (CHARLS) was utilized. In bi-directional analysis, we considered both single determinations and two successive determinations of CRP or depressive symptoms.Multivariate logistic regression assessed the association between elevated CRP levels at baseline or repeated episodes of CRP elevations over two successive determinations and subsequent elevated depressive symptoms, and vice versa.Results: Although single determinations of CRP or depressive symptoms yielded non-significant results in both directions, full multivariate models, adjusting for baseline depressive symptoms, socio-demographic characteristics, health-related behaviors, metabolic measures, and health status, revealed a significantly positive association based on two successive determinations of CRP or depressive symptoms. This significant association was observed between cumulative effects of sustained CRP elevations over two successive determinations (2 vs. 0) and subsequent elevated depressive symptoms (OR=1.58; 95% CI: 1.15 to 2.17) and between cumulative effect of repeated episodes of depression (2 vs. 0) and later elevated CRP (OR=1.26; 95% CI: 1.02 to 1.56).Furthermore, sex-stratified analyses confirmed the robustness of these relationships.There are bidirectional associations between depressive symptoms and CRP, driven by the cumulative effect of repeated episodes of CRP or depressive symptoms among middle-aged and older Chinese adults. These findings hold significant clinical implications, highlighting the potential of both anti-inflammatory and anti-depression approaches.